Kompetensi Penulis Popmama IDN Media dan Minat Baca Mahasiswa Fikom Untar - Yovianny, Laurentia; Yoedtadi, Moehammad Gafar (Koneksi, 2025)
Popmama IDN Media is one of the leading digital platforms in Indonesia, focusing on content related to family life, pregnancy, health, lifestyle, parenting, and various other topics. The writing ability of a creative writer plays a crucial role in enhancing the quality of content, driving innovation in news delivery, and attracting readers to engage with a story every day. Reading interest is a strong and deep attention, accompanied by a feeling of pleasure in reading activities, which can invite someone and increase their interest in reading on their own accord, without coercion. Researchers aim to determine the extent to which the competence of creative writers at Popmama IDN Media influences the reading interests of Fikom Untar students. By using a quantitative approach and survey techniques, questionnaires were distributed to Fikom Untar students. Data analysis of 100 respondents using the SPSS version. 29. In the correlation coefficient results, a positive relationship is obtained. It can be said that an increase will also follow every increase in Creative Writer Competence in Reading Interest. The results of the coefficient of determination showed that Creative Writer Competence had a 58.8% effect on Reading Interest. Popmama IDN Media, adalah salah satu platform digital di Indonesia yang berfokus pada konten seputar kehidupan keluarga, kehamilan, Kesehatan, gaya hidup, parenting, dan berbagai topik lainnya. Kemampuan menulis seorang penulis kreatif berperan sangat penting untuk meningkatkan kualitas konten, inovasi dalam penyampaian berita, dan menarik minat pembaca untuk membaca sebuah berita setiap harinya. Minat baca adalah suatu perhatian yang kuat dan mendalam, juga diikuti dengan perasaan senang dengan kegiatan membaca sehingga dapat mengajak seseorang dan meningkatkan minat baca seseorang dengan kemauannya sendiri tanpa paksaan. Peneliti ingin mengetahui seberapa besar pengaruh kompetensi penulis kreatif di Popmama IDN Media terhadap minat baca mahasiswa Fikom Untar. Dengan menggunakan pendekatan kuantitatif dan dengan menggunakan teknik survei dengan cara menyebarkan kuesioner yang ditujukan kepada mahasiswa Fikom Untar. Analisis data terhadap 100 responden menggunakan aplikasi SPSS ver. 29. Pada hasil koefisien korelasi, diperoleh hubungan yang bersifat positif. Hal ini dapat dikatakan setiap kenaikan dari Kompetensi Penulis Kreatif akan diikuti juga pada kenaikan dari Minat Baca. Pada hasil koefisien determinasi, diperoleh bahwa Kompetensi Penulis Kreatif berpengaruh sebesar 58,8% terhadap Minat Baca.